Scabies - Steer, Andrew (Henry Stewart Talks, 2023)
Scabies, Biology and transmission of scabies, Pathogenesis and complications of scabies, Epidemiology and clinical manifestations of scabies, Diagnosis and treatment of scabies, Control strategies and programs for scabies